Description of Germ Count on Outpatient Ward Floors Before and After Mopping at Inche Abdoel Moeis Regional Hospital - Siti Nurazisah Syarifuddin; Askur; Sresta Azahra (Afiyatun Journal of Health Sciences, 2026)
Background: Hospital environmental cleanliness is an important indicator in preventing Health-Care Associated Infections (HAIs). Outpatient rooms are high-traffic service areas with a high potential for floor contamination by microorganisms. This study aimed to describe the germ count on outpatient room floors before and after mopping at Inche Abdoel Moeis Regional Hospital, Samarinda. Methods: This study used a descriptive quantitative method with a cross-sectional approach. Samples consisted of 22 floor swab specimens from 11 outpatient clinics, including samples before and after mopping. Sampling was carried out using purposive sampling. Floor swab samples were cultured on Plate Count Agar (PCA) media through serial dilutions of 10⁻¹, 10⁻², and 10⁻³, then incubated at 35°C for 24–48 hours. Bacterial colonies were counted using a colony counter and calculated as Total Plate Count in CFU/cm². Results: The average germ count before mopping was 1.15 CFU/cm² and decreased to 0.40 CFU/cm² after mopping. The highest pre-mopping value was found in sample P1 at 5.8 CFU/cm², while the highest post-mopping value was found in sample P3 at 1.3 CFU/cm². All samples both before and after mopping were still below the hospital floor sanitation quality standard of ≤10 CFU/cm². A total of 100% of samples met the health requirements. Conclusion: Mopping was able to reduce the floor germ count in most outpatient rooms. Although several rooms showed slight increases after mopping, all outpatient room floors still met the sanitation standard based on the Regulation of the Minister of Health of the Republic of Indonesia Number 7 of 2019.